Processing Presuppositions and Implicatures: Similarities and Differences - Bill, Cory; Romoli, Jacopo; Schwarz, Florian (Frontiers in Communication, 2018)
Presuppositions and scalar implicatures are traditionally considered to be distinct phenomena, but recent accounts analyze (at least some of) the former as the latter. All else being equal, this “scalar implicature approach to presuppositions” predicts uniform behavior for the two types of inferences. Initial experimental studies comparing them yielded conflicting results. While some found a difference in the Response Time (RT) patterns of scalar implicatures and presuppositions, others found them to be uniform. We argue that the difference in outcomes is attributable to a difference in the type of response being measured: RTs associated with acceptance and rejection responses seem to pattern in opposite ways. Next, we report on a series of experiments to support this, and to compare the behavior of the two inferences more comprehensively. Experiments Ia and Ib look at both acceptance and rejection responses for both inference types, and find uniform patterns once the acceptance vs. rejection variable is factored in. Experiment II adds a new dimension by testing for the influence of prosody on the two inference types, and in this regard a clear difference between them emerges, posing a first substantive challenge to the scalar implicature approach to presuppositions. A third set of experiments investigates yet another prediction of this approach, according to which the presuppositional inference is introduced as a simple entailment in affirmative contexts. This predicts that these presuppositional inferences behave parallel to other entailments. Experiment IIIa compares rejections of affirmative sentences based on either their presuppositional inference or their entailed content and finds that they differ, with greater RTs for the former. As an additional control, Experiments IIIb and IIIc test for parallel differences between two entailments associated with always, which yield uniform results. In sum, while Experiments Ia and Ib are in line with previous findings that presuppositions and scalar implicatures under negation show uniform response time patterns, the differences found in Experiments II and IIIa-c pose a substantial challenge to approaches assimilating the two phenomena, while being entirely in line with the traditional perspective of seeing them as distinct.